The JCMT nearby galaxies legacy survey: SCUBA-2 observations of nearby galaxies. Issue 2 (7th March 2023) - Pattle, Kate; Gear, Walter; Wilson, Christine D
ABSTRACT: We present 850 μ m observations of a sample of 8 nearby spiral galaxies, made using the SCUBA-2 camera on the James Clerk Maxwell Telescope (JCMT) as part of the JCMT Nearby Galaxies Legacy Survey (NGLS). We corrected our data for the presence of the 12 CO J = 3 → 2 line in the SCUBA-2 850 μ m bandwidth using NGLS HARP data, finding a typical 12 CO contribution of ∼20 per cent. We measured dust column densities, temperatures, and opacity indices by fitting spectral energy distributions constructed from SCUBA-2 and archival Herschel observations, and used archival GALEX and Spitzer data to make maps of surface density of star formation (Σ _SFR ). Typically, comparing SCUBA-2-derived H2 surface densities (Σ _H_2 ) to Σ _SFR gives shallow star formation law indices within galaxies, with SCUBA-2-derived values typically being sublinear and Herschel -derived values typically being broadly linear. This difference is likely due to the effects of atmospheric filtering on the SCUBA-2 data. Comparing the mean values of Σ _H_2 and Σ _SFR of the galaxies in our sample returns a steeper star formation law index, broadly consistent with both the Kennicutt–Schmidt value of 1.4 and linearity. Our results show that a SCUBA-2 detection is a good predictor of star formation. We suggest that Herschel emission traces gas in regions which will form stars on time-scales ∼5 − 100 Myr, comparable to the star formation time-scale traced by GALEX and Spitzer data, while SCUBA-2 preferentially traces the densest gas within these regions, which likely forms stars on shorter time-scales.